Fleet assignment and bank structure integration in airline scheduling problem - Çiftçi, Muharrem Enis (My University, 2021)
In hub and spoke airline networks, flight arrivals and departures generally have a bank structure to increase connections among spoke cities through a hub airport in order to provide cheaper service for higher volumes of air traffic. Main objective of this thesis is to determine that routes in the banks are planned with the correct aircraft type, right departure and arrival time so as to maximize the passenger flow and the revenue flow of all destinations across the network and to fit the slot capacity of hub airport. In the first part of this thesis, Airline planning process and its subproblems are defined. Airline bank optimization problem which is a particular flight scheduling problem is introduced. A mathematical model is formulated for improving connection times among connecting flights by changing departure or arrival times of flights in a bank structure. The mathematical model aims to minimise the total waiting times for transfer passengers and generates flight schedules regarding slot constraints in the hub airports. Since the problem is NPhard, Simulated annealing and the tabu search algorithms are adopted to solve the bank optimization problem. A real-world application with a major Turkish carrier dataset which has a bank structure that connects Middle East and Europe flights is presented. The comparative results are promising for the airlines bank structure optimization. In the second part of this thesis, airline bank optimization problem is integrated with fleet assignment problem. A particular flight scheduling problem is combined with a strategic airline planning problem concurrently in the airline industry. It has been aimed to provide clean-state schedules instead of providing incremental update. Lastly, real-world case study is repeated using the same dataset for bank optimization to exhibit the competence of the integrated model on generating schedules that outperform existing schedules.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2021
Keywords: Airline scheduling problem; Bank optimization; Fleet assignment; Integrated approach; Metaheuristic algorithms